Bulk food purchase: The effect of food package waste literacy, a deontic perspective of justice, anticipated emotions, and subjective norms - Bernardinus Maria Purwanto; Rokhima Rostiani; Yulia Arisnani Widyaningsih; Ignasius Radix A.P. Jati (Cogent Business & Management, 2023)
This study aims to understand the forming mechanism of intention to buy bulk food at a bulk store. We examine the influence of positive and negative anticipated emotions and subjective norms on such intention. Further, we also investigate how anticipated emotions are influenced by a deontic perspective of justice and food package waste literacy. We conducted an online survey involving 301 respondents who had no prior experience of buying bulk food at a bulk store. Utilizing PLS-based structural equation modeling, we found that positive anticipated emotions and subjective norms directly influence intention. Further, we also found food package waste literacy to influence moral outrage, moral responsibility, and moral accountability which then partially influence positive and negative anticipated emotions. These findings contribute to the discussion of the dual mechanism to increase individual intention to buy bulk food at a bulk store. The positive approach suggests that literacy, a deontic perspective of justice, and positive anticipated emotions significantly influence intention. The stricter approach suggests the intensified influence of relevant others directly affects intention. These findings provide further guidance for government to increase environmental, specifically food package waste, literacy and to facilitate a community of practice to promote a positive view of pro-environmental behavior.
Keywords: 650; anticipated emotions; bulk store; deontic justice; food package waste; intention; literacy